CONFRONTING THE ABSURD: FROM CAMUS TO BECKETT: EXPLORING THE STRUGGLE FOR MEANING IN EXISTENTIAL WORKS - Sharma, Aabroo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Absurdism is a philosophical school of thought which states that the efforts of humanity in finding a meaning will eventually fail and life does and always will embody uncertainty and scepticism, a belief that the universe is chaotic, disorganised, essentially a muddle, absolutely devoid of any purpose and meaning. Any attempt in finding a true meaning would be proved ineffectual. The similar contention has been effectively put by Martin Esslin in his celebrated essay ‘Theatre of the Absurd’-The meaning of the term absurd is ‘out of harmony with reason or propriety; illogical’ (Esslin 23).